The Revenger’s Tragedy: Date, Title, Theatre, Text - Holdsworth, Roger (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2022)
As well as fixing a precise date for the play, this study of The Revenger’s Tragedy offers new evidence for identifying it as the supposedly lost The Viper and Her Brood. The reattribution implies that its traditional title is spurious, and the belief that it was written for the King’s Men and performed at the Globe is mistaken. It was a Blackfriars play, and commissioned by Robert Keysar, manager of the Blackfriars Children. The essay also examines current editorial responses to the play’s text, noting places where commentary is needed but absent, or offered but erroneous.